A preliminary results of integrated chemotherapy with EGFR receptor tyrosine kinase inhibitors in patients with non-small-cell-lung cancer harboring EGFR mutation - K. K. Laktionov; D. I. Yudin; V. V. Breder; E. V. Reutova; K. P. Laktionov; D. T. Marinov; D. A. Peregudov; M. S. Ardzinba (Медицинский совет, 2019)
In the open prospective non-randomized single-center study we recruited patients with advanced NSCLC harboring EGFR mutations. Initially there were two months of treatment by gefitinib 250 mg daily. Then, after a 2-week drug-free period, 3 cycles of paclitaxel 175 mg / m2 and carboplatin AUC5 were administrated at days 71-113. Thereafter, gefitinib was re-started on day 135 and continued until disease progression. The primary endpoint was progressive free survival (PFS) time. One-year PFS in all patients group included in the study at the time of the preliminary analysis was 79.8%, median PFS was 17 months (13.5–23, CI 95%). In the group of integrated chemotherapy one-year PFS was 89.3%, median PFS was 19 months (14–23.5, CI 95%).